Pemodelan Data Aplikasi Tiket Bioskop Berbasis Mobile Menggunakan ERD, CDM, dan PDM - Nahda Nur Fadillah; Erlis Krisda Yanti Halawa; Cicilya Setyani; Zatin Niqotaini (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2025)
The process of booking movie tickets, especially through mobile platforms, has experienced significant transformations due to advances in information technology. This study intends to model a mobile-based cinema ticket booking information system using a structured approach that employs Entity Relationship Diagram (ERD), Conceptual Data Model (CDM), and Physical Data Model (PDM). Identifying system requirements, designing logical entities and relationships, and creating a physical database structure that is ready to use are all approaches used. The results show that clarifying the data structure and improving the efficiency of system development can be achieved by applying the three models integratively. In an effective movie theater ticket booking system, the created model has shown the real business relationships between buyers, tickets, movies, administration, and payment.